Isolation of 5,7-dihydroxy-8-methoxyflavone as an anti-hyperglycemic agent from the leaves of Tetracera indica MERR. (Mempelas) - Ahmed, Qamar Uddin; Dogarai, Bashar Bello S.; Latip, Jalifah; Mat So'ad, Siti Zaiton; Umar, Abdulrashid (2011)
The present study was carried out to scientifically prove the traditional claim of Tetracera indica Merr. which is used extensively in folk medicine as a remedy for diabetes in Malaysia. Aqueous (AQ) and methanolic (MEOH) extracts of the leaves of T. indica were prepared and experiments were conducted in vivo using animal model. Glucose levels in male albino rats (SD strain) with hyperglycemia induced by alloxan monohydrate (160 mg/kg b.w.) were determined after the oral administration of the aqueous AQ and MEOH extracts. Two doses of each extract (250 and 500 mg/kg b.w.) were evaluated. Both extracts exhibited significant anti-hyperglycemic activity in alloxan induced diabetic rats, however in normal rats no hypoglycemic activity was observed, when compared with both +ve and –ve controlled groups. The antidiabetic activity was also found to be comparable to that of the effect produced by glibenclamide (GLBC) (0.25 mg/kg b.w.). The LD50 of both extracts was found to be more than 5000 mg/kg body weight and no lethal toxicity was observed within this range. MEOH extract of the leaves of T. indica upon repeated coloumn choromatography and recrystallization techniques afforded a major phenolic compound viz., 5,7-dihydroxy-8-methoxyflavone (1.2 gm) (Fig. 1) which revealed significant anti-hyperglycemic activity comparable to GLBC in vivo. Structure of biologically active compound was thoroughly elucidated through extensive spectroscopic (NMR, IR, UV and MASS) analysis. This study justifies the use of T. indica by the local herbalists to treat diabetes in Malaysia.